Sexual and Reproductive Health Services Utilization and Associated Factors among College Students at West Arsi Zone in Oromia Region, Ethiopia - Demelash Wachamo; Yadessa Tegene; Abdisa Tibeso; Assefa Washo (The Scientific World Journal)
Background. Young people are challenged with sexual and reproductive health (SRH) problems due to limited access to services and information. It contributes a high burden of sexually transmitted disease, unsafe abortion, and premature mortality, especially in low-income countries like Ethiopia. Hence, this study aimed at assessing the SRH service utilization and associated factors among college students at West Arsi Zone in Oromia region, Ethiopia. Methods. Institutional-based cross-sectional study was conducted among 519 randomly selected college students from January 01, 2019, up to April 30, 2019. Data were collected through self-administered pretested questionnaires. Data entry and analysis for descriptive and logistic regression models were performed by using SPSS (version 23). The result was declared as statistically significant at p < 0.05. Results. The utilization of at least one SRH service in the last twelve months was seen in 304 (58.6%) students. Mainly information and counseling (81.3%), voluntary testing and counseling for HIV (80.6%), condom service (37.2%), pregnancy test (35.5%), family planning services (33.2%), and abortion care services (26.0%) were most frequently utilized. The students’ aged between 20 and 24 years [AOR = 2.05, 95% CI: 1.38–3.06], female students [AOR = 1.92, 95% CI: 1.30–2.82], those not living with family [AOR = 1.54, 95% CI: 1.05–2.26], those who discussed about SRH with family/friends [AOR = 1.92, 95% CI: 1.31–2.82], and those who participated in school clubs [AOR = 1.75, 95% CI: 1.19, 2.58] more frequently used SRH service compared with their counterparts. Conclusions. The utilization of SRH services was low when compared with other studies and needs improvements to tackle RH-related problems. It requires pertinent health education and the SRH club at higher educational institutions is crucial.